PENERAPAN METODE PEMBELAJARAN DIFERENSIASI PROGRESIF BERBANTUAN LKS UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS X MIPA 3 SMA TAMAN RAMA DENPASAR TAHUN PELAJARAN 2019/2020 - Surat, I Made (LP2M IKIP PGRI Bali, 2019)
This study aims to find out whether the progressive diffraction learning method assisted by LKS can increase the activeness and achievement of mathematics learning students of X MIPA 3 in Taman Rama Denpasar High School in learning mathematics in 2019/2020 academic year. This type of research is classroom action research. Activities undertaken are the application of progressive differential learning processes in which they are the object of research as well. Student analysis is the process of learning activities carried out descriptively. The grouping activities are based on the ideal mean and standard ideal deviation. The average value of students is 9.79 where student activity is still quite high and needs to be improved the average value of learning outcomes is 6.48 the ability of students to catch is 64.8% and student completeness. learning 20.6% mastery learning classical students under 85%. Can be categorized or categorized. In the second cycle, the average value of student learning activities was 16.8, an increase of 6.88 compared to the average value of student learning activities in the first cycle. The average value of student learning activities is 8021, the ability to capture (DS) is 80.1% and mastery learning (KB) is 85.7%. In the second cycle, the average value of learning outcomes, students' ability to capture, and completeness of students who study classically achieve criteria according to the stated curriculum. The application of progressive differentiation learning models assisted by LKS in mathematics learning can increase the activeness and learning achievement of students of Mathematics X MIPA 3 at Taman Rama Denpasar.